KEKUATAN HUKUM TRANSAKSI JUAL BELI ONLINE YANG DILAKUKAN SISWA MAN DAERAH ISTIMEWA YOGYAKARTA - Siregar, Ahmad Munawir (Fakultas Hukum Universitas Muhammadiyah Cirebon, 2023)
Electronic transactions or buying and selling online are very popular among students. Until now there are no rules regarding age limits in electronic transactions or buying and selling online so that students or teenagers can make electronic transactions. This study aims to find out and analyze the regulation of online buying and selling transactions carried out by students or teenagers so that they can determine the legal consequences of online buying and selling transactions carried out by students or teenagers. The results showed that most of the MAN students in the Yogyakarta area had made buying and selling transactions through online shops. Even though the ITE Law doesn’t set an age limit for online buying and selling transactions, online buying and selling transactions are still subject to the Civil Code. Online buying and selling transactions carried out by students or teenagers have violated subjective requirements, giving rise to the legal consequences of electronic contracts. The need for special rules regarding age limits in electronic transactions and settlement mechanisms if one of the parties is a student or teenager who is not old enough. Keywords : transactions, buying and selling online, teenagers.